2013
DOI: 10.3390/w5041472
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of DOM and Removal of DBPs Precursors across O3-BAC Integrated Treatment for the Micro-Polluted Raw Water of the Huangpu River

Abstract: Abstract:The aim of this study is to determine the impact upon dissolved organic matter (DOM) and removal of disinfection by-product (DBP) precursors of adding an ozone-biological activated carbon (O 3 -BAC) process after the conventional treatment process (CTP) using water from the Huangpu River in Shanghai, east China. Several metrics, including size fractionation, dissolved organic carbon (DOC) and trihalomethane formation potential (THMFP), were employed to accomplish this goal. In the raw water collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In this study, however, AOC produced by ozonation is composed of low molecular weight and non-aromatic organic compounds [17,19,43,48,49]. So, physical interaction may be more important than hydrophobic interaction in adsorbing those low molecular weight and hydrophilic AOC compounds by GAC.…”
Section: Effect Of Temperature On Aoc Adsorption By Filter Mediamentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, however, AOC produced by ozonation is composed of low molecular weight and non-aromatic organic compounds [17,19,43,48,49]. So, physical interaction may be more important than hydrophobic interaction in adsorbing those low molecular weight and hydrophilic AOC compounds by GAC.…”
Section: Effect Of Temperature On Aoc Adsorption By Filter Mediamentioning
confidence: 87%
“…molecular weight and biodegradable organic matters, e.g., aldehydes, ketones, ketoacids and carboxylic acids [14,16,17,19,20,36,43,48,49]. In the YWTP, AOC increase was high from May to November, but low in winter (January to March).…”
Section: Aoc Formation By Ozonationmentioning
confidence: 99%
“…This paper addresses a gap in the literature, as there is a paucity of studies on drinking water policy alternatives in Romania, despite the paramount importance of the subject. Although abundant research is dedicated to various aspects of drinking water treatment [8][9][10], including a similar dual perspective (economic-technical and/or conventional-green), the joining of a conventional and an environmentally friendly technology in the framework of a public policy analysis dedicated especially to PDP rural areas in Romania gives originality to the present paper. In general, three types of impact-economic, social and environmental-are analyzed in order to have a sustainable public policy, and here the first one was taken under scrutiny.…”
Section: Goals and Noveltymentioning
confidence: 99%
“…Little influence of ambient conditions on COD Mn removal in Ditch A was observed during the same experimental runs. Some references [31,34] have found that small molecules dominated the total dissolved organic matter (DOM) in the Huangpu River, with pesticides, herbicides, and phytohormones detected at high levels, and these small compounds contributed more than 55% of the dissolved organic pollutants in raw water from the Huangpu River. In general, the absorption process and biochemical reactions on ecological revetments were insufficient to remove these small organic compounds [38] and thus led to a lower COD Mn removal rate than that for nutrient pollutants in the same experimental runs.…”
Section: Differences In Water Purification Effects Due To Operationalmentioning
confidence: 99%
“…Over the years, the Huangpu River provides the major source of water for Shanghai, the largest city in China, however, the water quality of the Huangpu River have showed a decreasing trend of deterioration recently [30,31,34], and concentration values of COD Mn , ammonia, and TP in the Huangpu River frequently exceeded 6.0, 1.0, and 0.2 mg/L, respectively, which were standard limited values of water quality grade III for potable water sources according to China Environmental Quality Standards for Surface Water (GB3838-2002) [35]. Therefore, a pre-treating drinking water had to be exerted on raw water from the Huangpu River aiming to guaranteeing drinking water safety.…”
Section: Introductionmentioning
confidence: 99%